A method for detecting and evaluating the impact performance of a laminate containing an elastomer

By designing a detection method, through impact test and macroscopic analysis, combined with evaluation methods, and using a variety of performance parameters, the problem of insufficient research methods for low-speed impact performance of laminated sheet materials in the existing technology is solved, and a more accurate and objective impact performance evaluation is achieved.

CN115855623BActive Publication Date: 2025-03-11HARBIN INST OF TECH AT WEIHAI +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211545497.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-05
Publication Date
2025-03-11
Estimated Expiration
2042-12-05

AI Technical Summary

Technical Problem

The prior art lacks methods when studying the low-speed impact properties of laminated sheet materials, and the data processing is not effective enough to provide objective evaluation.

Method used

A detection method is designed to obtain load-time, load-displacement and energy-time curves through impact tests, and the impact performance of the laminate is determined in combination with macroscopic analysis. At the same time, an evaluation method is provided to judge the effectiveness of the impact performance of the laminated plate by a variety of performance parameters.

Benefits of technology

It improves the accuracy of detection, provides objective and accurate evaluation, and can quickly and effectively evaluate the impact performance of laminated plates containing elastomers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115855623B_ABST
    Figure CN115855623B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for detecting the impact performance of a laminate containing an elastomer, comprising: step one, performing an impact test on the laminate containing an elastomer to obtain a load-time curve, a load-displacement curve and an energy-time curve; step two, obtaining a variety of performance parameters from the load-time curve, the load-displacement curve and the energy-time curve; step three, obtaining the anti-interference ability, the ability to ensure structural integrity, the mitigation ability, the anti-deformation ability and the ability to absorb impact energy of the laminate containing the elastomer according to the various performance parameters. The present invention also discloses a method for evaluating the impact performance of a laminate containing an elastomer, by performing an impact test under constant impact mass conditions, obtaining a load-time curve, a load-displacement curve and an energy-time curve, thereby evaluating the impact performance of the laminate containing an elastomer by a variety of performance parameters. The present invention has the characteristics of higher accuracy and wider applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite material performance research, and more specifically, to a method for detecting and evaluating the impact performance of a laminate containing an elastomer. Background Art

[0002] Composite materials are new materials that are made by optimizing the combination of material components with different properties using advanced material preparation technology. They can give full play to the advantages of various materials, overcome the defects of single materials, and expand the application range of materials.

[0003] Fiber metal laminates are a combination of fiber reinforced polymer and metal sheets that can now be found in various aerospace applications. As a type of composite material, hybrid laminates containing elastomers have many advantages. For example, carbon laminated aluminum reinforced epoxy is relatively new and shows higher specific mechanical properties compared to glass laminated aluminum reinforced epoxy commonly used in the industry. However, the combination of aluminum sheets with carbon fibers usually leads to galvanic corrosion at the interface. The large mismatch in the thermal expansion coefficients between these materials leads to high residual stresses after curing in the hot mold. One possible way to solve this problem is to introduce an elastic interlayer between the aluminum sheet and the carbon fiber reinforced polymer layer. This method can prevent galvanic corrosion and also adjust the damping behavior and impact properties. After adding the elastic layer, the properties of this new material should be studied to verify whether it meets the requirements.

[0004] At present, the research on the mechanical response of laminate materials under impact is relatively rough, mainly focusing on high-speed research, lacking research on low-speed impact, and the data processing methods after the experiment are insufficient, and the experimental results cannot be effectively analyzed and objective evaluation cannot be provided. Summary of the invention

[0005] The purpose of the present invention is to design and develop a method for testing the impact performance of a laminate containing an elastomer, obtain detailed data and curves through impact tests, and determine the impact performance of the laminate containing an elastomer in combination with a macroscopic analysis of the curve, thereby improving the accuracy of the detection.

[0006] Another object of the present invention is to design and develop a method for evaluating the impact performance of elastomer-containing laminates, which judges the quality of the impact performance of elastomer-containing laminates through multiple performance parameters, provides objective and accurate evaluation, and is quick and effective.

[0007] The technical solution provided by the present invention is:

[0008] A method for testing the impact performance of a laminate containing an elastomer comprises the following steps:

[0009] Step 1: Perform an impact test on the laminate containing the elastomer to obtain a load-time curve, a load-displacement curve and an energy-time curve;

[0010] Step 2: obtaining a variety of performance parameters from the load-time curve, load-displacement curve and energy-time curve;

[0011] Step three: obtaining the anti-interference ability, structural integrity ensuring ability, relaxation ability, deformation resistance and impact energy absorption ability of the elastomer-containing laminate according to the multiple performance parameters.

[0012] Preferably, the impact test shown includes: a constant impact mass condition, a constant impact velocity condition and / or a constant impact energy condition, and the constant impact mass condition, the constant impact velocity condition and the constant impact energy condition can all obtain a load-time curve, a load-displacement curve and an energy-time curve.

[0013] Preferably, the constant impact mass working condition includes: large-mass constant impact and small-mass constant impact;

[0014] The large mass constant impact specifically includes the following process:

[0015] An impactor with a hammer mass of 2 kg and a hammer diameter of 20 mm is used to impact the elastomer-containing laminate at an impact speed of 1 m / s, 2 m / s, 3 m / s, 4 m / s or 5 m / s;

[0016] The small mass constant impact specifically includes the following process:

[0017] An impactor with a hammer mass of 0.1 kg and a hammer diameter of 10 mm is used to impact the elastomer-containing laminate at an impact speed of 1 m / s, 5 m / s, 10 m / s, 15 m / s or 20 m / s;

[0018] The constant impact velocity working condition specifically includes the following process:

[0019] The impact speed is constant at 2 m / s, and an impactor with a hammer head diameter of 20 mm and a hammer head mass of 2 kg, 4 kg, 6 kg, 8 kg or 10 kg is used to impact the laminate containing the elastomer;

[0020] The constant impact energy working condition includes:

[0021] The impact energy is constant at 20 J, and impactors with a hammer head diameter of 20 mm and a hammer head mass of 3 kg, 4 kg, 5 kg, 6 kg or 7 kg are used to impact the elastomer-containing laminate at impact speeds of 3.65 m / s, 3.16 m / s, 2.82 m / s, 2.58 m / s and 2.39 m / s respectively.

[0022] Preferably, the plurality of performance parameters include: initial impact load, peak impact load, maximum deformation degree, final deformation degree, impact bending stiffness, initial impact energy and final impact energy.

[0023] Preferably, the greater the initial impact load, the stronger the anti-interference ability;

[0024] The greater the peak impact load, the stronger the ability to ensure structural integrity;

[0025] The greater the impact bending rigidity, the stronger the anti-deformation ability;

[0026] The smaller the absorbed energy ratio, the stronger the mitigation capability;

[0027] The greater the elastic strain energy, the stronger the impact energy absorption capability.

[0028] Preferably, it also includes:

[0029] Step 4: Establish a finite element model of the laminate containing the elastomer, obtain response data, and supplement the impact performance of the laminate containing the elastomer.

[0030] Preferably, the response data includes:

[0031] The plastic deformation dissipated energy of the metal layer of the elastomer-containing laminate, the degree of interlayer delamination damage of the composite material layer and the degree of matrix damage within the composite material layer.

[0032] A method for evaluating the impact performance of a laminate containing an elastomer, using the method for detecting the impact performance of a laminate containing an elastomer, comprises the following steps:

[0033] Step 1: performing a large-mass constant impact or a small-mass constant impact impact test on the laminate containing the elastomer to obtain a load-time curve, a load-displacement curve and an energy-time curve;

[0034] Step 2: obtaining an initial impact load and a peak impact load according to the load-time curve, obtaining a maximum deformation degree, a final deformation degree and an impact bending stiffness according to the load-displacement curve, and obtaining an initial impact energy and a final impact energy according to the energy-time curve;

[0035] Step 3: When the large mass is constantly impacted and the impact energy is 25J:

[0036] If F inc <2000N, the anti-interference ability of the laminate containing the elastomer is poor;

[0037] If 2000N≤Finc ≤3000N, the anti-interference ability of the laminate containing the elastomer is medium;

[0038] If F inc >3000N, the anti-interference ability of the laminate containing the elastomer is strong;

[0039] If F max <4000N, the ability of the laminate containing the elastomer to ensure structural integrity is poor;

[0040] If 4000N≤F max ≤5000N, the ability of the laminate containing the elastomer to ensure structural integrity is medium;

[0041] If F max >5000N, the laminate containing the elastomer has a strong ability to ensure structural integrity;

[0042] When a large mass constant impact with an impact energy of 16J:

[0043] If K bs <400Nmm, the elastic body-containing laminate has poor deformation resistance;

[0044] If 400Nmm≤K bs ≤650Nmm, the deformation resistance of the laminate containing the elastomer is medium;

[0045] If K bs >650Nmm, the elastic body-containing laminate has a strong ability to resist deformation;

[0046] When a large mass constant impact with an impact energy of 9J:

[0047] If da >0.8, the relaxation ability of the laminate containing the elastomer is poor;

[0048] If 0.6≤λ da ≤0.8, the relaxation capacity of the elastomer-containing laminate is medium;

[0049] If da <0.6, the relaxation ability of the laminate containing the elastomer is strong;

[0050] If W < 1J, the elastic body-containing laminate has poor impact energy absorption capability;

[0051] If 1J≤W≤3J, the impact energy absorption capacity of the laminate containing the elastomer is medium;

[0052] If W>3J, the elastic body-containing laminate has a strong ability to absorb impact energy;

[0053] When a small mass is constantly impacted and the impact energy is 5J:

[0054] If F inc <1000N, the anti-interference ability of the laminate containing the elastomer is poor;

[0055] If 1000N≤F inc ≤1700N, the anti-interference ability of the laminate containing the elastomer is medium;

[0056] If F inc >1700N, the anti-interference ability of the laminate containing the elastomer is strong;

[0057] If F max <2000N, the ability of the laminate containing the elastomer to ensure structural integrity is poor;

[0058] If 2000N≤F max ≤3500N, the ability of the laminate containing the elastomer to ensure structural integrity is medium;

[0059] If F max >3500N, the elastic body-containing laminate has a strong ability to ensure structural integrity;

[0060] Among them, F inc is the initial impact load, F max is the peak impact load, K bs is the impact bending stiffness, λ da is the ratio of energy absorbed by deformation and damage, and W is the elastic strain energy.

[0061] Preferably, the impact bending stiffness is the slope of the initial segment of the load-displacement curve;

[0062] The elastic strain energy is the difference between the initial impact energy and the final impact energy.

[0063] Preferably, it also includes:

[0064] Step 4: Supplement and verify the evaluation of the impact performance of the elastomer-containing laminate under constant impact velocity and constant impact energy conditions, specifically including:

[0065] Performing an impact test on the laminate containing the elastomer under a constant impact velocity condition to obtain a load-time curve;

[0066] When the impact velocity is constant and the impact energy is 20J:

[0067] If t < 0.001 s, the impact performance of the elastomer-containing laminate is unstable;

[0068] If 0.001s≤t≤0.003s, the impact performance of the laminate containing the elastomer is relatively stable;

[0069] If t≥0.003s, the impact performance of the elastomer-containing laminate is stable;

[0070] Step 5: Obtain response data of the finite element model of the laminate containing the elastomer under a large mass constant impact. If the large mass constant impact and the impact energy are 25J:

[0071] If E pla >8J, the performance of the laminate containing the elastomer changes greatly after the impact;

[0072] If 5J≤E pla ≤8J, the performance change of the elastomer-containing laminate after impact is moderate;

[0073] If E pla <5J, the performance change of the elastomer-containing laminate after impact is small;

[0074] If SDEG>2.5J, the interlayer bonding energy of the composite material of the laminate containing the elastomer is low;

[0075] If 1.5 J ≤ SDEG ≤ 2.5 J, the interlayer bonding energy of the composite material of the laminate containing the elastomer is medium;

[0076] If SDEG < 1.5 J, the interlayer bonding energy of the composite material of the laminate containing the elastomer is high;

[0077] If HSNMTCRT>2J, the composite material of the laminate containing the elastomer has large intra-layer damage;

[0078] If 1J≤HSNMTCRT≤2J, the composite material of the laminate containing the elastomer has moderate intra-layer failure;

[0079] If HSNMTCRT<1J, the composite material of the elastomer-containing laminate has little intra-layer damage.

[0080] Among them, E pla is the plastic deformation dissipated energy of the bottom metal layer of the laminate containing elastomer relative to the impact surface, SDEG is the interlaminar delamination damage degree of the composite layer, and HSNMTCRT is the intralaminar matrix damage degree of the composite layer.

[0081] The beneficial effects of the present invention are:

[0082] (1) The present invention designs and develops a method for detecting the impact performance of a laminate containing an elastomer and a method for evaluating the same. Through impact tests under three different working conditions, objective and detailed experimental data and curves are obtained. The obtained curves can be systematically analyzed macroscopically to obtain changes in important parameters of the material when it is impacted, and physical quantities that affect the impact performance of the laminate material containing an elastic layer are proposed, providing an objective and effective method for selecting elastomer materials in composite materials.

[0083] (2) The detection method and evaluation method for the impact performance of the laminate containing elastomer designed and developed by the present invention, in addition to conducting a macroscopic analysis to draw preliminary conclusions, also conducts a microscopic study on the damage assessment, deformation degree and energy absorption of each layer of the material after the impact, thereby combining the macroscopic analysis with the microscopic analysis to obtain a more accurate mechanical response of the laminate material containing elastomer when subjected to impact. BRIEF DESCRIPTION OF THE DRAWINGS

[0084] Figure 1 The figure is a schematic flow chart of the method for evaluating the impact performance of a laminate containing an elastomer according to the present invention.

[0085] Figure 2 Schematic diagram of the structure of the laminate containing elastomer in the embodiment of the present invention.

[0086] Figure 3 Schematic diagram of the Ft curve of HyCEML under large-mass constant impact in the embodiment of the present invention.

[0087] Figure 4 Schematic diagram of the Fu curve of HyCEML under large mass constant impact in the embodiment of the present invention.

[0088] Figure 5 λ is the HyCEML in the embodiment of the present invention under large mass constant impact da With E imp Relationship diagram.

[0089] Figure 6 K is the K of HyCEML under large mass constant impact in the embodiment of the present invention. bs With E imp Relationship diagram.

[0090] Figure 7 Schematic diagram of the Et curve of HyCEML under large-mass constant impact in the embodiment of the present invention.

[0091] Figure 8 Schematic diagram of the Ft curve of HyCEML under constant impact velocity conditions in the embodiment of the present invention.

[0092] Fig. 9 Schematic diagram of the Ft curve of HyCEML under constant impact energy conditions in the embodiment of the present invention.

[0093] Fig.10 Graph showing the plastic deformation of the metal layer in the HyCEML finite element model in the embodiment of the present invention.

[0094] Fig.11 Graph showing the relationship between the plastic deformation degree of the metal layer and the impact energy in the HyCEML finite element model in the embodiment of the present invention.

[0095] Fig.12 Schematic diagram of the damage condition of the interface between the internal 0° and 90°C FRP plies in the HyCEML finite element model in the embodiment of the present invention.

[0096] Fig.13 Graph showing the relationship between damage energy and impact energy at the interface between internal 0° and 90°C FRP plies in the HyCEML finite element model in the embodiment of the present invention.

[0097] Fig.14 Schematic diagram of damage of intra-layer loss of composite materials in the HyCEML finite element model in the embodiment of the present invention.

[0098] Fig.15 Graph showing the relationship between the damage energy lost within the composite layer and the impact energy in the HyCEML finite element model in the embodiment of the present invention. DETAILED DESCRIPTION

[0099] The present invention is further described in detail below so that those skilled in the art can implement it according to the description.

[0100] The present invention provides a method for testing the impact performance of a laminate containing an elastomer, which studies the different responses of the laminate containing an elastomer under different impacts, processes the data, summarizes the specific parameters that can represent the impact performance of the material, and finally obtains the impact performance of the laminate containing an elastomer. Specifically, it includes the following steps:

[0101] Step 1, performing an impact test on the laminate containing the elastomer to obtain a load-time (Ft) curve, a load-displacement (Fu) curve and an energy-time (Et) curve;

[0102] Wherein, the laminate containing elastomer is composed of three different layers, and the three different layers include: a metal layer, a composite material layer and an elastic layer;

[0103] Impact tests include: constant impact mass condition, constant impact velocity condition and / or constant impact energy condition. All three conditions can obtain load-time curve, load-displacement curve and energy-time curve;

[0104] As a preference, in a specific implementation, only one working condition may be used to test the main impact properties of the laminate containing the elastomer, and other working conditions may be used to supplement and verify the impact properties, so as to save the testing time;

[0105] Step 2: obtaining a variety of performance parameters from the load-time curve, load-displacement curve and energy-time curve;

[0106] Specific:

[0107] Under the condition of constant impact mass, the initial impact load F is obtained through the load-time curve. inc and peak impact load F max , the maximum deformation degree U of the material is obtained through the load-displacement curve max , the final deformation degree of the material U t , and thus the ratio of energy absorbed by material deformation and damage can be obtained da , and then define the initial slope of the curve as the impact bending stiffness K bs ; Obtain the initial impact energy E of the material through the energy-time curve imp and final impact energy E abs , and the initial impact energy E imp and final impact energy E abs The elastic strain energy W of the material is calculated from the difference.

[0108] Under the condition of constant impact velocity, the difference in mechanical response under different impact energies is independent of the strain rate, that is, the time when the material reaches the peak load and the duration of the impact can be obtained.

[0109] Under the condition of constant impact energy, by observing the load-time curve, the oscillation degree of the curve can be obtained, and then the impact performance of the material can be judged.

[0110] Step 3: obtaining the anti-interference ability, structural integrity guarantee ability, relaxation ability, deformation resistance and impact energy absorption ability of the laminate containing the elastomer according to the multiple performance parameters, that is, obtaining the impact performance of the laminate containing the elastomer;

[0111] Among them, the larger the initial impact load, the stronger the anti-interference ability; the larger the peak impact load, the stronger the ability to ensure structural integrity; the larger the impact bending stiffness, the stronger the anti-deformation ability; the smaller the energy absorption ratio, the stronger the mitigation ability; the larger the elastic strain energy, the stronger the ability to absorb impact energy;

[0112] Step 4: simulate the material of the laminate containing the elastomer, study the damage and energy absorption of each layer of the material during the impact process from a microscopic perspective, and then supplement the impact performance of the laminate containing the elastomer;

[0113] Specifically, the laminate material containing the elastomer is modeled in the Abaqus software (version 2020), and the material is impacted using the impact test parameter settings in the above steps to obtain response data, and the impact performance of the laminate containing the elastomer is supplemented, specifically including:

[0114] (1) Analysis of plastic deformation of metal layer:

[0115] When the material is subjected to a large-mass impact, the plastic deformation of the metal layer at the same position of the material and the plastic deformation strain values ​​of the metal layer at the surface and bottom of the material are analyzed, and the energy dissipated by the plastic deformation of the metal layer when the material is subjected to different impact sizes is compared; when the material is subjected to a small-mass impact, since the hammer head diameter of the impactor used is small, attention must be paid to the hidden danger of metal layer fracture during the experiment. Before the metal layer is obviously fractured, the plastic deformation strain value of the metal layer and its dissipated energy are also observed;

[0116] (2) Observe the damage to the interface between composite plies under impact:

[0117] Under the three working conditions of the impact test, the damage of the interface between the internal 0° and 90° composite plies was observed and analyzed using the delamination damage degree (SDEG), where the SDEG value ranges from 0 to 1, with 0 representing no damage and 1 representing complete delamination. The differences in energy dissipation between the composite plies of the laminate material were compared, and the energy dissipation proportion of each layer under different impact energies was plotted and statistically analyzed;

[0118] (3) Analysis of intralayer damage including matrix and fiber:

[0119] When the laminate is subjected to different impact energies, the damage of the interface between the internal 0° and 90°C FRP layers is observed and statistically analyzed, the degree of matrix damage is calculated (the value range is from 0 to 1, 0 represents no damage, and 1 represents complete damage), the dissipated energy of the material is analyzed, and the degree of influence of the elastomer on the dissipated energy of the composite layer is obtained.

[0120] In step 1, the constant impact mass working condition specifically includes a large-mass constant impact and a small-mass constant impact, the mass of the large-mass impactor is 2kg, the mass of the small-mass impactor is 0.1kg, and the laminate material containing the elastomer is impacted at different speeds; the constant impact speed working condition is to use impactors of different masses to impact the laminate material containing the elastomer at the same speed; the constant impact energy working condition is to select different impact masses and impact speeds in combination while ensuring that the impact energy remains unchanged;

[0121] In this embodiment, the specific parameter settings of the impact mass constant working condition are shown in Table 1:

[0122] Table 1 Test parameters of constant impact mass condition

[0123]

[0124] The specific parameter settings for the constant impact velocity condition are shown in Table 2:

[0125] Table 2 Test parameters of constant impact velocity condition

[0126]

[0127]

[0128] The specific parameter settings for the constant impact energy condition are shown in Table 3:

[0129] Table 3 Test parameters of constant impact energy condition

[0130]

[0131] In the actual testing of the impact properties of materials, several samples in the test conditions can be selected for testing to obtain representative parameters.

[0132] like Figure 1 As shown, the present invention provides a method for evaluating the impact performance of a laminate containing an elastomer, and the method for detecting the impact performance of a laminate containing an elastomer specifically comprises the following steps:

[0133] Step 1, performing an impact test on the laminate containing the elastomer from the top of the laminate under a constant impact mass condition to obtain a load-time (Ft) curve, a load-displacement (Fu) curve and an energy-time (Et) curve;

[0134] Among them, because the constant impact mass working condition is divided into two types: large mass constant impact and small mass constant impact, therefore, in the process of impact performance evaluation, one of the impact tests is arbitrarily selected.

[0135] Step 2: obtaining an initial impact load and a peak impact load according to the load-time curve, obtaining a maximum deformation degree, a final deformation degree and an impact bending stiffness according to the load-displacement curve, and obtaining an initial impact energy and a final impact energy according to the energy-time curve;

[0136] Step 3: Select representative impact energies in the impact test for evaluation. The parameters of other impact energy acquisition can be omitted because the changes are too subtle:

[0137] For the Ft curve, first observe the smoothness of the curve. The oscillation of the curve represents the progressive loss inside the laminate. The smoother the curve, the more stable the material is inside during impact. Then measure the specific parameter F on the Ft curve. inc (initial impact load) and F max (peak impact load), they are both important parameters to measure the impact resistance. According to their sizes, the maximum impact force when the material is not affected by the impact and the impact force when the material structure is destroyed can be obtained. Among them, when the large mass constant impact and the impact energy is 25J:

[0138] If F inc <2000N, the anti-interference ability of the laminate containing the elastomer is poor, and the performance of the material is insufficient to meet the normal working requirements;

[0139] If 2000N≤F inc ≤3000N, the anti-interference ability of the laminate containing the elastomer is medium, and the material can work normally under specific application conditions;

[0140] If F inc >3000N, the anti-interference ability of the laminate containing the elastomer is strong, and the material can work unaffectedly under most working conditions;

[0141] If F max <4000N, the ability of the laminate containing the elastomer to ensure structural integrity is poor, and the performance of the material is insufficient to meet normal working requirements;

[0142] If 4000N≤F max ≤5000N, the ability of the laminate containing the elastomer to ensure structural integrity is medium, and the material can ensure structural integrity under specific application conditions;

[0143] If F max >5000N, the elastic body-containing laminate has a strong ability to ensure structural integrity, and the material structure will not be easily damaged under various working conditions;

[0144] When a small mass is constantly impacted and the impact energy is 5J:

[0145] If F inc <1000N, the anti-interference ability of the laminate containing the elastomer is poor;

[0146] If 1000N≤F inc ≤1700N, the anti-interference ability of the laminate containing the elastomer is medium;

[0147] If F inc >1700N, the anti-interference ability of the laminate containing the elastomer is strong;

[0148] If F max <2000N, the ability of the laminate containing the elastomer to ensure structural integrity is poor;

[0149] If 2000N≤F max ≤3500N, the ability of the laminate containing the elastomer to ensure structural integrity is medium;

[0150] If F max >3500N, the elastic body-containing laminate has a strong ability to ensure structural integrity;

[0151] The Fu curve reflects the relationship between the load on the material and the deformation of the material. The maximum deformation U of the laminate material can be obtained on the curve. max And the final deformation of the laminate U t After obtaining two eigenvalues, calculate the ratio U of the two t U max , which represents the ratio of energy absorbed by deformation and damage da , the ratio is between 0 and 1, and when this value is smaller, it means that the dissipated energy is smaller, and the elastic part of the laminate material absorbs a greater proportion of energy through deformation and damage. When a large mass constant impact and the impact energy is 9J:

[0152] If da >0.8, the relaxation ability of the laminate containing the elastomer is poor;

[0153] If 0.6≤λ da ≤0.8, the relaxation capacity of the elastomer-containing laminate is medium;

[0154] If da <0.6, the relaxation ability of the laminate containing the elastomer is strong;

[0155] The slope of the initial segment of the Fu curve is defined as the impact bending stiffness K bs , which is an important quantitative parameter for evaluating the impact resistance of laminates, reflecting the ability of materials to resist impact deformation. When a large mass constant impact with an impact energy of 16J is applied:

[0156] If K bs <400Nmm, the elastic body-containing laminate has poor deformation resistance;

[0157] If 400Nmm≤K bs ≤650Nmm, the deformation resistance of the laminate containing the elastomer is medium;

[0158] If K bs >650Nmm, the elastic body-containing laminate has a strong ability to resist deformation;

[0159] The key to the Et curve lies in the direction of energy. The energy in the laminate containing elastomers is transferred from the kinetic energy of the drop weight. The energy in the laminate can be divided into six parts, including plastic deformation of metal, failure of metal, delamination and CFRP failure, viscosity of elastomer and elastic strain energy of component materials. After the impact, the energy of the first five parts will not be returned to the drop weight. This part of energy is called dissipated energy. After the impact, the drop weight rebounds and the elastic strain energy of the laminate will be returned to the drop weight. During the impact process, the dissipated energy and elastic strain energy are collectively referred to as the energy absorbed by the laminate. Two characteristic values ​​can be obtained in the Et curve, namely E and imp (initial impact energy) and E abs (final impact energy), the difference between the two is the elastic strain energy, which represents the ability of the elastic part of the laminate material to resist impact. By comparing the size of the elastic strain energy, the impact performance of the laminate material can be obtained. Generally speaking, the elastic strain energy is larger and is sufficient to withstand a larger impact. When a large mass constant impact and the impact energy is 9J:

[0160] If W < 1J, the elastic body-containing laminate has poor impact energy absorption capability;

[0161] If 1J≤W≤3J, the impact energy absorption capacity of the laminate containing the elastomer is medium;

[0162] If W>3J, the elastic body-containing laminate has a strong ability to absorb impact energy;

[0163] Among them, F inc is the initial impact load, F max is the peak impact load, K bs is the impact bending stiffness, λ da is the ratio of energy absorbed by deformation and damage, and W is the elastic strain energy.

[0164] The impact performance of the elastomer-containing laminate is preliminarily concluded from a comprehensive analysis of the five previously obtained capabilities: anti-interference ability, ability to ensure structural integrity, mitigation ability, anti-deformation ability, and ability to absorb impact energy. If all five capabilities are excellent, it means that the material has excellent impact performance; if none of the five capabilities is outstanding, it means that the material has average or even poor impact performance.

[0165] In actual applications, these five abilities should be evaluated separately according to specific needs to ensure that the required abilities are outstanding and the other abilities are not bad.

[0166] Step 4: Supplement and verify the evaluation of the impact performance of the elastomer-containing laminate under constant impact velocity and constant impact energy conditions. In practical applications, only the Ft curves under two conditions need to be considered, including:

[0167] (1) Curve analysis under constant impact velocity conditions:

[0168] Observe the Ft curve of the material and observe the duration t of the impact when the material reaches the peak load, that is, the time between reaching the peak load and the load starting to drop. This value represents the ability of the material to maintain its impact performance under impact. When the impact velocity is constant and the impact energy is 20J:

[0169] If t < 0.001 s, the impact performance of the elastomer-containing laminate is unstable;

[0170] If 0.001s≤t≤0.003s, the impact performance of the laminate containing the elastomer is relatively stable;

[0171] If t≥0.003s, the impact performance of the elastomer-containing laminate is stable;

[0172] Among them, the impact duration t is in the ms level, and the data curve can be directly displayed by a special drop hammer impact tester;

[0173] (2) Curve analysis when energy is constant:

[0174] Observe and analyze the Ft curve of the laminate material containing elastomer, and observe that after F inc After (initial impact load), the degree of oscillation of the curve represents the combined strength of the internal layers of the material. If the degree of oscillation is too large, the layout of the internal layer structure needs to be changed. Otherwise, even if the impact performance meets the requirements, the internal layers will fall off at the micro level when facing the impact, affecting the use;

[0175] The degree of oscillation is determined by the number of inflection points caused by the rising and falling changes of the curve between the initial impact load and the peak impact load. When the number of inflection points is not greater than 100, the degree of oscillation of the curve is acceptable.

[0176] Step 5: obtaining response data of the finite element model of the laminate containing the elastomer under a large-mass constant impact, mainly including the plastic deformation dissipation energy of the upper and lower metal layers of the laminate containing the elastomer, the interlayer delamination damage degree of the composite material layer, and the intralayer matrix damage degree of the composite material layer;

[0177] Among them, the plastic deformation dissipation energy of the metal layer of the material is analyzed. If a large mass constant impact and the impact energy is 25J:

[0178] If E pla >8J, the performance of the laminate containing the elastomer changes greatly after the impact, and the impact performance of the material will be greatly damaged after one impact, and it cannot be used for a long time;

[0179] If 5J≤E pla ≤8J, the performance change of the laminate containing the elastomer after impact is moderate, and the use of the material needs to be checked frequently to prevent sudden failure;

[0180] If E pla <5J, the performance change of the laminate containing the elastomer after the impact is small and the service life is long;

[0181] Analyze the damage of the interface between the composite material layers, study the energy dissipation ratio of each layer through images, and analyze the influence of the elastomer on the distribution of dissipated energy in the thickness direction. The dissipated energy of each layer should be as uniform as possible to avoid a situation where a certain layer bears a large amount of energy, and ensure that the material structure will not fall off during the impact. When the large mass constant impact and the impact energy are 25J:

[0182] If SDEG>2.5J, the bonding energy between the composite layers of the laminate containing the elastomer is low and it is very easy to be damaged;

[0183] If 1.5 J ≤ SDEG ≤ 2.5 J, the interlayer bonding energy of the composite material of the laminate containing the elastomer is medium;

[0184] If SDEG is less than 1.5 J, the interlayer bonding energy of the composite material of the laminate containing the elastomer is high, and interlayer shedding will not occur during the impact process;

[0185] The internal damage of the composite material ply was analyzed when a large mass constant impact with an impact energy of 25J was observed:

[0186] If HSNMTCRT>2J, the composite material of the laminate containing the elastomer has large intra-layer damage;

[0187] If 1J≤HSNMTCRT≤2J, the composite material of the laminate containing the elastomer has moderate intra-layer failure;

[0188] If HSNMTCRT<1J, the composite material of the elastomer-containing laminate has little intra-layer damage.

[0189] Among them, E pla is the plastic deformation dissipated energy of the bottom metal layer of the laminate containing elastomer relative to the impact surface, SDEG is the interlaminar delamination damage degree of the composite layer, and HSNMTCRT is the intralaminar matrix damage degree of the composite layer.

[0190] Comprehensive impact performance analysis of the laminate model containing elastomers ensures that the overall impact performance of the material will not be affected by the structure and interlayer energy at the microscopic level.

[0191] Among them, when conducting impact tests under constant impact mass conditions, there are two different impact types: large mass and small mass. If the target parameters obtained are the same, the parameters shall prevail; if the target parameters obtained are different, one of them shall be selected for testing based on what kind of impact the evaluated elastomer-containing laminate material faces more in application, that is, in the specific evaluation process, only one target parameter shall be selected for evaluation.

[0192] Example

[0193] The impact performance of a HyCEML (laminate material containing elastomer) under different impact load conditions was tested and evaluated:

[0194] like Figure 2 As shown, the laminate material containing an elastomer in this embodiment includes a surface aluminum layer, an elastic layer, a composite material layer, an elastic layer and a bottom aluminum layer. The HyCEML is subjected to impact tests under three working conditions:

[0195] (1) Impact mass constant condition:

[0196] For the constant impactor mass condition, since most materials are used in large-mass impact, the large-mass impact test is selected for the constant-mass experiment, and the detailed test parameters are shown in Table 1.

[0197] (2) Constant impact velocity condition:

[0198] For the constant impact velocity condition, the detailed test parameters are shown in Table 2. Compared with the constant impact mass condition, the impact velocity is constant and the difference in mechanical response under different impact energies is not related to the strain rate effect.

[0199] (3) Constant impact energy condition:

[0200] For the constant impact energy condition, the velocity and mass of the impactor change simultaneously, but a constant impact energy of 20 J is generated. The detailed test parameters are shown in Table 3.

[0201] After the impact test, the load-time (Ft) curve, load-displacement (Fu) curve and energy-time (Et) curve under the impact condition of constant impact mass, the load-time (Ft) curve under the impact condition of constant impact velocity and constant impact energy were obtained. Through these curves, the impact mechanical response was studied, and the impact performance was obtained and evaluated:

[0202] 1. Macro analysis:

[0203] (1) Constant quality condition:

[0204] like Figure 3 As shown in the figure, it is the Ft curve of HyCEML after being subjected to impact energy from 1J to 25J. It can be seen that when the impact energy is 25J, F inc The magnitude is 3100N, which is greater than 3000N, indicating that the laminate material has excellent anti-interference ability; when the impact energy is 25J, F max The size is 5200N, which is greater than 5000N, indicating that the laminate material structure will not be easily damaged under various working conditions and has excellent performance in ensuring structural integrity.

[0205] like Figure 4 The Fu curve of HyCEML after being subjected to impact energy from 1J to 25J is shown in Figure 2. Through analysis and calculation, the proportion of energy absorbed by material deformation and damage can be obtained. t U max The ratio of da ) and impact bending stiffness K bs (0-4mm is defined as the initial segment) and the impact energy relationship diagram, such as Figure 5 , Figure 6 As shown in the figure, it can be seen that when the impact energy is 9J, the proportion of energy absorbed by material deformation and damage is da The value is about 0.45, which is less than 0.6, indicating that when facing impact, the impact energy mitigated by the material is suitable for most applications and has excellent mitigation ability; when subjected to an impact energy of 15J, the impact bending stiffness K bs The size is about 700N / mm. When it is greater than 650N / mm, it means that the material has excellent anti-deformation ability.

[0206] like Figure 7The following is the Et curve of HyCEML after 1J to 25J impact energy. Under the impact energy of 9J, the initial impact energy E imp About 8.5J, the final energy value E abs The size is 5J, and the elastic strain energy W is 3.5J, which exceeds 3J. It can be said that the material has a relatively good ability to absorb impact energy.

[0207] Therefore, through preliminary analysis, the elastomer-containing laminate material HyCEML has excellent anti-interference ability, excellent structural integrity assurance performance, excellent mitigation ability, excellent deformation resistance and excellent impact energy absorption ability, so its impact performance is outstanding and sufficient to meet the requirements of most working conditions.

[0208] (2) Constant speed condition (only Ft curve is analyzed):

[0209] The Ft curve for constant speed conditions is as follows: Figure 8 As shown, it can be seen that when the impact energy is 20J, the peak load is reached at 0.0045s, and at 0.0085s, the curve has a downward trend. The impact duration t is 0.004s, which is greater than 0.003s, indicating that the impact performance stability of the elastomer-containing laminate material is good.

[0210] (4) Constant energy condition (only Ft curve is analyzed):

[0211] The Ft curve of the constant energy condition is as follows: Fig. 9 As shown, it can be seen that after F inc After (initial impact load), the curve drops slightly and then quickly rebounds without large fluctuations, which means that the combined strength of the internal layers of the material is sufficient, and no microscopic damage will occur during impact. The macroscopic impact performance has sufficient toughness and is not restricted by the structure.

[0212] 2. Micro analysis:

[0213] (1) Analysis of plastic deformation of metal layer:

[0214] like Fig.10 As shown in the figure, the plastic strain (PEEQ) of the upper and lower aluminum alloy layers when the laminate containing elastomer is impacted by a constant large mass impactor with different impact energies. It is found in the figure that with the increase of impact energy, the plastic strain of the aluminum alloy layer gradually increases, and the plastic strain value of the upper surface layer aluminum alloy is higher than that of the lower surface layer aluminum alloy.

[0215] like Fig.11As shown, it can be seen that when the impact energy is 25J, the plastic deformation energy of the metal layer at the bottom of the material is about 3.3J, which is less than 5J, indicating that after the impact, the impact performance of the material does not change much and the service life is guaranteed.

[0216] (2) Observe the damage of the composite material layer under impact:

[0217] like Fig.12 As shown in the figure, the damage of the interface between the internal 0° and 90° CFRP layers under different impact energies of a large-mass impactor is shown. The delamination damage degree (SDEG) ranges from 0 to 1, where 0 represents no damage and 1 represents complete delamination. The internal delamination area of ​​FML and HyCEML increases with the increase of impact energy. The introduction of elastomer not only prevents the delamination between aluminum alloy and CFRP, but also reduces the delamination damage between 0° and 90°FRP.

[0218] like Fig.13 As shown in the figure, under the impact energy of 25J, the delamination energy of each layer is relatively uniform and meets the requirements. The total delamination damage is about 1.3J, which is less than 1.5J, indicating that the bonding energy between the layers is sufficient and no interlayer detachment will occur during the impact.

[0219] (3) Analysis of intra-layer losses including matrix and fiber:

[0220] like Fig.14 As shown in Figure 3, the internal CFRP matrix damage of HyCEML under different impact energies of a large mass impactor is shown. The matrix damage degree HSNMTCRT ranges from 0 to 1, where 0 represents no damage and 1 represents complete damage.

[0221] like Fig.15 As shown in the figure, under the impact energy of 25J, the total intra-layer damage is about 0.9J. When it is less than 1J, no delamination failure will occur during the impact.

[0222] In summary, by designing impact tests under three different working conditions, and then analyzing the obtained load-time (Ft) curve, load-displacement (Fu) curve and energy-time (Et) curve, we obtained parameters that can characterize the material properties, and preliminarily determined that the material's impact performance is relatively good.

[0223] At the micro level, the analysis mainly focuses on the energy display diagram when subjected to force. The damage and energy dissipation of each layer of the laminate material containing elastomers are analyzed through Abaqus software. It is concluded that the bonding energy between the material layers is sufficient and no delamination damage will occur. The macro impact performance is supported from the micro level, and the degree of plastic deformation ensures a long service life. Therefore, the material has excellent impact performance and a long service life.

[0224] The present invention designs and develops a method for detecting the impact performance of a laminate containing an elastomer and a method for evaluating the same. By studying the parameters that can characterize the impact performance, the pros and cons of the impact performance can be concluded, thereby providing an objective evaluation for the selection of materials. It also provides a set of objective and effective evaluation methods for the main impact mechanical responses, a method for processing and summarizing the parameters that can characterize the impact performance of the laminate material, and a corresponding verification method at the microscopic level to ensure the parameter analysis results, thereby selecting the application field suitable for the material.

[0225] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A method for testing the impact performance of a laminate containing an elastomer, characterized in that: The steps include: Step 1: Perform an impact test on the laminate containing the elastomer to obtain a load-time curve, a load-displacement curve and an energy-time curve; The impact test includes: a constant impact mass condition, a constant impact velocity condition and / or a constant impact energy condition, and the constant impact mass condition, the constant impact velocity condition and the constant impact energy condition can all obtain a load-time curve, a load-displacement curve and an energy-time curve; The constant impact mass working condition includes: large-mass constant impact and small-mass constant impact; The large mass constant impact specifically includes the following process: An impactor with a hammer mass of 2 kg and a hammer diameter of 20 mm is used to impact the elastomer-containing laminate at an impact speed of 1 m / s, 2 m / s, 3 m / s, 4 m / s or 5 m / s; The small mass constant impact specifically includes the following process: An impactor with a hammer mass of 0.1 kg and a hammer diameter of 10 mm is used to impact the elastomer-containing laminate at an impact speed of 1 m / s, 5 m / s, 10 m / s, 15 m / s or 20 m / s; The constant impact velocity working condition specifically includes the following process: The impact speed is constant at 2 m / s, and an impactor with a hammer head diameter of 20 mm and a hammer head mass of 2 kg, 4 kg, 6 kg, 8 kg or 10 kg is used to impact the laminate containing the elastomer; The constant impact energy working condition includes: The impact energy is constant at 20 J, and an impactor with a hammer head diameter of 20 mm and a hammer head mass of 3 kg, 4 kg, 5 kg, 6 kg or 7 kg is used to impact the elastomer-containing laminate at impact speeds of 3.65 m / s, 3.16 m / s, 2.82 m / s, 2.58 m / s and 2.39 m / s respectively; Step 2: obtaining a variety of performance parameters from the load-time curve, load-displacement curve and energy-time curve; The various performance parameters include: initial impact load, peak impact load, maximum deformation degree, final deformation degree, impact bending stiffness, initial impact energy and final impact energy; Step three: obtaining the anti-interference ability, structural integrity ensuring ability, relaxation ability, deformation resistance and impact energy absorption ability of the elastomer-containing laminate according to the multiple performance parameters.

2. The method for testing the impact performance of a laminate containing an elastomer according to claim 1, characterized in that: The larger the initial impact load is, the stronger the anti-interference capability is; The greater the peak impact load, the stronger the ability to ensure structural integrity; The greater the impact bending rigidity, the stronger the anti-deformation ability; The smaller the absorbed energy ratio, the stronger the mitigation capability; The greater the elastic strain energy, the stronger the impact energy absorption capability.

3. The method for testing the impact performance of a laminate containing an elastomer according to claim 2, characterized in that: Also includes: Step 4: Establish a finite element model of the laminate containing the elastomer, obtain response data, and supplement the impact performance of the laminate containing the elastomer.

4. The method for testing the impact performance of a laminate containing an elastomer according to claim 3, characterized in that: The response data includes: The plastic deformation dissipated energy of the metal layer of the elastomer-containing laminate, the degree of interlayer delamination damage of the composite material layer and the degree of matrix damage within the composite material layer.

5. A method for evaluating the impact performance of a laminate containing an elastomer, using the method for detecting the impact performance of a laminate containing an elastomer as claimed in any one of claims 1 to 4, characterized in that: The steps include: Step 1: performing a large-mass constant impact or a small-mass constant impact impact test on the laminate containing the elastomer to obtain a load-time curve, a load-displacement curve and an energy-time curve; Step 2: obtaining an initial impact load and a peak impact load according to the load-time curve, obtaining a maximum deformation degree, a final deformation degree and an impact bending stiffness according to the load-displacement curve, and obtaining an initial impact energy and a final impact energy according to the energy-time curve; Step 3: When the large mass is constantly impacted and the impact energy is 25J: If F inc <2000N, the anti-interference ability of the laminate containing the elastomer is poor; If 2000N≤F inc ≤3000N, the anti-interference ability of the laminate containing the elastomer is medium; If F inc >3000N, the anti-interference ability of the laminate containing the elastomer is strong; If F max <4000N, the ability of the laminate containing the elastomer to ensure structural integrity is poor; If 4000N≤F max ≤5000N, the ability of the laminate containing the elastomer to ensure structural integrity is medium; If F max >5000N, the elastic body-containing laminate has a strong ability to ensure structural integrity; When a large mass constant impact with an impact energy of 16J: If K bs <400N / mm, the elastic body-containing laminate has poor deformation resistance; If 400N / mm≤K bs ≤650N / mm, the deformation resistance of the laminate containing the elastomer is medium; If K bs >650N / mm, the elastic body-containing laminate has a strong ability to resist deformation; When a large mass constant impact with an impact energy of 9J: If da >0.8, the relaxation ability of the laminate containing the elastomer is poor; If 0.6≤λ da ≤0.8, the relaxation capacity of the elastomer-containing laminate is medium; If da <0.6, the relaxation ability of the laminate containing the elastomer is strong; If W < 1J, the elastic body-containing laminate has poor impact energy absorption capability; If 1J≤W≤3J, the impact energy absorption capacity of the laminate containing the elastomer is medium; If W>3J, the elastic body-containing laminate has a strong ability to absorb impact energy; When a small mass is constantly impacted and the impact energy is 5J: If F inc <1000N, the anti-interference ability of the laminate containing the elastomer is poor; If 1000N≤F inc ≤1700N, the anti-interference ability of the laminate containing the elastomer is medium; If F inc >1700N, the anti-interference ability of the laminate containing the elastomer is strong; If F max <2000N, the ability of the laminate containing the elastomer to ensure structural integrity is poor; If 2000N≤F max ≤3500N, the ability of the laminate containing the elastomer to ensure structural integrity is medium; If F max >3500N, the elastic body-containing laminate has a strong ability to ensure structural integrity; Among them, F inc is the initial impact load, F max is the peak impact load, K bs is the impact bending stiffness, λ da is the ratio of energy absorbed by deformation and damage, and W is the elastic strain energy.

6. The method for evaluating the impact performance of an elastomer-containing laminate according to claim 5, wherein: The impact bending stiffness is the slope of the initial segment of the load-displacement curve; The elastic strain energy is the difference between the initial impact energy and the final impact energy.

7. The method for evaluating the impact performance of an elastomer-containing laminate according to claim 6, wherein: Also includes: Step 4: Supplement and verify the evaluation of the impact performance of the elastomer-containing laminate under constant impact velocity and constant impact energy conditions, specifically including: Performing an impact test on the laminate containing the elastomer under a constant impact velocity condition to obtain a load-time curve; If the impact speed is constant and the impact energy is 20J: If t < 0.001 s, the impact performance of the elastomer-containing laminate is unstable; If 0.001s≤t≤0.003s, the impact performance of the laminate containing the elastomer is relatively stable; If t≥0.003s, the impact performance of the elastomer-containing laminate is stable; Step 5: Obtain response data of the finite element model of the laminate containing the elastomer under a large mass constant impact. If the large mass constant impact and the impact energy are 25J: If E pla >8J, the performance of the laminate containing the elastomer changes greatly after the impact; If 5J≤E pla ≤8J, the performance change of the elastomer-containing laminate after impact is moderate; If E pla <5J, the performance change of the elastomer-containing laminate after impact is small; If SDEG>2.5J, the interlayer bonding energy of the composite material of the laminate containing the elastomer is low; If 1.5 J ≤ SDEG ≤ 2.5 J, the interlayer bonding energy of the composite material of the laminate containing the elastomer is medium; If SDEG < 1.5 J, the interlayer bonding energy of the composite material of the laminate containing the elastomer is high; If HSNMTCRT>2J, the composite material of the laminate containing the elastomer has large intra-layer damage; If 1J≤HSNMTCRT≤2J, the composite material of the laminate containing the elastomer has moderate intra-layer failure; If HSNMTCRT<1J, the composite material of the laminate containing the elastomer has small intra-layer damage; Among them, E pla is the plastic deformation dissipated energy of the bottom metal layer of the laminate containing elastomer relative to the impact surface, SDEG is the interlaminar delamination damage degree of the composite layer, and HSNMTCRT is the intralaminar matrix damage degree of the composite layer.

Citation Information

Patent Citations

  • High impact strength, elastic, composite, fibre, metal laminate

    AU2004313609A1

  • Measurement method of residual compression strength of composite material laminated board containing impact damages

    CN102607935A